Completion of an Online Library Module Improves Engineering Student Performance on Information Literacy Skills Tests - Rachel E. Scott (Evidence Based Library and Information Practice, 2016)
A Review of: Zhang, Q., Goodman, M., & Xie, S. (2015). Integrating library instruction into the Course Management System for a first-year engineering class: An evidence-based study measuring the effectiveness of blended learning on students’ information literacy levels. College & Research Libraries, 76(7), 934-958. http://dx.doi.org/10.5860/crl.76.7.934